Emotional Intelligence, Emotional Regulation Strategies, and Subjective Well-Being Among University Teachers: A Moderated Mediation Analysis - Sha, Jingrong; Tang, Tianqi; Shu, Hong; He, Kejian; Shen, Sha (Frontiers in Psychology, 2022)
This study aimed to explore the mediating role of emotional regulation strategies in the relationship between emotional intelligence and subjective well-being among Chinese university teachers, and evaluate whether effort-reward imbalance moderated the mediating effect of emotional regulation strategies. A total of 308 Chinese university teachers were recruited for this study. The results showed that emotional regulation strategies played a partial mediating role in the relationship between emotional intelligence and subjective well-being. Moreover, an effort-reward imbalance moderated the relationship between emotional regulation strategies and subjective well-being. For individuals with more balanced perceptions, emotional intelligence had a significant effect on subjective well-being via cognitive reappraisal, while for individuals with more imbalanced perceptions, emotional intelligence did not have a significant effect on subjective well-being via cognitive reappraisal. These findings provide a better understanding of the effects of emotional intelligence and emotional regulation strategies on subjective well-being, which could provide interventions for promoting subjective well-being among teachers.